2017
DOI: 10.2495/cc170131
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Urban Quality of Life: A Case Study of a Coastal City in the Metropolitan Area of Rome

Abstract: The present paper concerns an environmentally sustainable neighborhood planning project, as part of the smart community, located in the municipality of Ladispoli, in the Metropolitan area of Rome, along the Tyrrhenian coast. The project was designed as a solution to two current issues, involving all the major urban areas of the Northern Hemisphere: the ageing population and the young New Immigrants Citizens integration; the purpose is, therefore, to create an intergenerational space of mutual support and excha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 3 publications
(3 reference statements)
0
14
0
Order By: Relevance
“…On a wider territorial scale, the fundamental role of cities is widely recognized in the literature; in [31] it was found that on an urban scale, problems can be tackled more effectively by the easier communication with local decision makers; in [32][33][34] the problem of energy self-sufficiency at municipal level was addressed, identifying solutions to increase the RES share on the electricity consumption; in [35] the possibility of using municipal waste was evaluated, for building envelopes for nZEB; in [36] a methodology was proposed for the preparation of an urban action plan based on carbon footprint assessment related to a city in southern Italy; in other works, the field of study was more limited and reached the neighbourhood scale [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…On a wider territorial scale, the fundamental role of cities is widely recognized in the literature; in [31] it was found that on an urban scale, problems can be tackled more effectively by the easier communication with local decision makers; in [32][33][34] the problem of energy self-sufficiency at municipal level was addressed, identifying solutions to increase the RES share on the electricity consumption; in [35] the possibility of using municipal waste was evaluated, for building envelopes for nZEB; in [36] a methodology was proposed for the preparation of an urban action plan based on carbon footprint assessment related to a city in southern Italy; in other works, the field of study was more limited and reached the neighbourhood scale [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the diverse benefits of contact with nature to an ageing population and the many possibilities smart technologies provide for bringing nature inside, this review shows that opportunities for challenging, boundary-spanning research approaches to one of the most pressing societal challenges of our times are many. Bentsen et al (2009) x x Bentsen et al (2010) x Bernatzky (1975) x 2013x x Debele (2014) Moffat et al (2009) x Villeneuve et al 2012x Younan et al (2016) x x Almeter et al 2018x GPS Astell-Burt et al 2016x GPS x Barbosa et al (2007) x GPS x Battisto et al 2018x x x Benmarhnia et al 2017x Bunney et al (2016) x GPS Burgoine et al 2015x GPS Cassarino et al 2019x x Chien et al 2019GPS x Cochrane et al (2009) x GPS x Coutts et al (2010) x GPS x Cui et al (2013) x Cumo et al (2017) x x Dadvand et al (2017) x Douglas et al (2018) x GPS x Forsyth and Crewe (2010) x Gao et al (2012) x Germann- Chiari and Seeland (2004) x GPS x Gose et al (2013) GPS Graça et al (2018) x x Green et al (2016) x Haggag (2010) x Hermida et al (2017) x GPS x Hillsdon et al (2006) x GPS x Hoffimann et al 2017x GPS Huang et al (2018) x x Hui et al (2017) x Jamaludin et al (2014) x Janssen and Rosu (2015) x GPS Jim and Chen (2007) x Jim and Shan (2013) x x Jones 2018x…”
Section: Discussionmentioning
confidence: 99%
“…In this context, for a correct energy requalification of the existing building patrimony, guidelines and good practices will have to be developed to adapt the patrimony to modern needs of use and comfort and to adapt buildings to climate change [8]; wherever possible, efforts should be made to achieve the nZEB standard [9][10][11], with an integrated restructuring, which takes into account Indoor Environmental Quality (IEQ) [12], which includes the exploitation of renewable energy resources, with the introduction of automation systems for the management of flexible loads [13,14]; particular attention must be paid to the buildings subject to protection, for which an improvement in performance will be sought, in compliance with historical and architectural values [15][16][17], a massive intervention in the energy upgrade of the cultural heritage is necessary not to vain the efforts made in recent decades to achieve the objectives of the EU's "Climate Change Package" [18]. In an urban environment, the use of those energy vectors that allow limiting local polluting emissions should be preferred [19][20][21].…”
Section: Introductionmentioning
confidence: 99%